Оптимізація системи зберігання ігрових цінностей в іграх жанру RPG - Кіслов, Д. Р. (ХНУРЕ, 2023)
This work is devoted to optimizing the process of storing m-game values in RPG games, namely, the storage of items in the inventory and related virtual containers that are typical for games of this genre. An analysis of popular games using item storage mechanics was carried out in order to establish the optimal set of tools necessary for the player to access them conveniently and intuitively. It has been established that the most optimal is a set of two virtual containers, the main of which is a static inventory container with features characteristic of the game genre, as well as a special container that unifies access to some in-game objects that have storage properties.